Regular and Young Investigator Award Abstracts 2021
DOI: 10.1136/jitc-2021-sitc2021.410
|View full text |Cite
|
Sign up to set email alerts
|

410 Phase I interim study results of Nous-209, an off-the-shelf immunotherapy, with pembrolizumab, for the treatment of tumors with a deficiency in mismatch repair/microsatellite instability (dMMR/MSI)

Abstract: BackgroundDefective DNA mismatch repair (dMMR) leads to high levels of microsatellite-instability (MSI-H) and insertions or deletions in coding regions, resulting in the generation of tumor-specific frameshift peptides (FSPs). We selected 209 shared FSPs among subjects with first- or second-line metastatic dMMR/MSI-H colorectal (CRC), gastric, and gastroesophageal junction (GEJ) cancers, to develop an off-the-shelf vaccine for the treatment of dMMR/MSI-H tumors. Selected FSPs were cloned into four proprietary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…49 While intriguing preliminary findings, it is too early to parse out if the favorable responses can be attributed to Nous-209 or pembrolizumab, but nonetheless, this trial demonstrates that FSP vaccines are safe and tolerable. 49 An additional clinical trial utilized three FSPs recurrently found in MMRd colorectal and endometrial cancers to assess safety and efficacy of FSP in the clinic. These FSPs-TAF1B, HT001/ASTE1, and AIM2-all of which are derived from cMS indels, were administered to 22 patients with a past medical history or current diagnosis of MMRd CRC.…”
Section: Preclinical and Clinical Studies Of Targeting Neoantigens In...mentioning
confidence: 82%
See 2 more Smart Citations
“…49 While intriguing preliminary findings, it is too early to parse out if the favorable responses can be attributed to Nous-209 or pembrolizumab, but nonetheless, this trial demonstrates that FSP vaccines are safe and tolerable. 49 An additional clinical trial utilized three FSPs recurrently found in MMRd colorectal and endometrial cancers to assess safety and efficacy of FSP in the clinic. These FSPs-TAF1B, HT001/ASTE1, and AIM2-all of which are derived from cMS indels, were administered to 22 patients with a past medical history or current diagnosis of MMRd CRC.…”
Section: Preclinical and Clinical Studies Of Targeting Neoantigens In...mentioning
confidence: 82%
“…Recently reported interim data shows that of the 12 patients enrolled to the trial, 7 have shown partial responses and 2 now have stable disease, while the remaining 3 have had disease progression. 49 While intriguing preliminary findings, it is too early to parse out if the favorable responses can be attributed to Nous-209 or pembrolizumab, but nonetheless, this trial demonstrates that FSP vaccines are safe and tolerable. 49 An additional clinical trial utilized three FSPs recurrently found in MMRd colorectal and endometrial cancers to assess safety and efficacy of FSP in the clinic.…”
Section: Preclinical and Clinical Studies Of Targeting Neoantigens In...mentioning
confidence: 82%
See 1 more Smart Citation
“…A similar approach is also currently employed to target shared neoantigens in metastatic patients with a deficiency in mismatch repair/microsatellite instability (dMMR/MSI) [ 31 ]. Recently published data from the latter trial showed robust and broad induction of neoantigen-specific CD8 T-cell response in vaccinated cancer patient [ 32 ▪ , 33 ]. Moreover, expansion and diversification of vaccine-induced T-cell recognizing neoantigens were observed post-treatment in the tumor infiltrate in patients with a long-term clinical response [ 32 ▪ ].…”
Section: Clinical Trial Landscape Of Neoantigen-based Vaccines In Mel...mentioning
confidence: 99%
“…Importantly, the combination treatment was reported to be safe, tolerable and immunogenic for T cells as shown by ex-vivo IFNg ELISpot. 117 However, because the study used combination therapy, how much of the response was attributable to pembrolizumab and how much to the Nous-209 vaccine is unclear at present. Future clinical trials for Lynch syndrome vaccines need to address safety and efficacy to reduce the burden of cancers and advanced neoplasia.…”
Section: Preclinical and Clinical Experiencementioning
confidence: 99%